(untitled) (Annual of the Faculty of Philosophy in Skopje, 2020)
Globally, in the last few decades, the professional treatment of a child with a disability has taken on a different philosophical perspective, that is, from an individual to a complex holistic approach to the whole family. In the modern approach of familyoriented early intervention, particular important is the mutual cooperation between the experts, that is the transdisciplinary model, where the team of expert’s transdisciplinary measures provides services aimed to the family and child. Those services are coordinated and integrated to better respond to the complex needs of the child with a disability and his/her family. For decades, Republic of Macedonia has been facing problems in early detection process and early treatment of people with disabilities. In this direction, we conducted research of 47 families who have a child with a disability. The aim of the research was to detect when they noticed the first problems, who noticed them and when they started with the treatment. According to the results in 80% of the sample, the first signs of atypical development were noticed by parents (more often by mothers), and in 57% of the children the treatment started one or more years after receiving the diagnosis. We believe that the problems with early intervention can be overcome by following the trend of family-oriented early intervention, greater support for families and involvement of the family educator as part of the professional team.